AB1076 Ultrasound Abnormalities at the Entheses are not an Uncommon Finding in Patients with Rheumatoid Arthritis. (9th June 2015) - Andersen, M.D.; Petersen, S.J.; Axelsen, M.B.; Østergaard, M.; Hetland, M.; Hansen, M.S.; Poggenborg, R.P.; Terslev, L.
Abstract : Background: Enthesitis are frequently occurring in spondyloarthritis and are considered a hallmark of the disease. However, little is known of the occurrence of entheseal abnormalities in other rheumatic conditions such as rheumatoid arthritis (RA). Clinical evaluation of entheseal involvement is often difficult and ultrasound (US) has been shown to be more sensitive than clinical evaluation. Objectives: To describe the occurrence of entheseal abnormalities by US in patients with RA using B-mode and Doppler US. Methods: Patients with active RA according to the ACR criteria were included. All patients were examined by US using a GE LOGIQ 9 with a 14 MHz linear array transducer, a Doppler frequency of 7.5 MHz and Doppler settings adjusted to slow flow according to published recommendations. For each patient 10 entheseal sites were examined bilaterally by US: Quadriceps tendon, superior and inferior insertion of the patella tendon, Achilles tendon, proximal insertion of the plantar fascia, common extensor and flexor tendon insertion at the elbow, triceps tendon insertion on olecranon, gluteal muscle insertion onto the greater trochanter and supraspinatus tendon insertion. Each entheseal site was scored for US signs of enthesitis: bone erosion, thickened enthesis/loss of fibrillar structure, calcifications/enthesophytes and Doppler signal. Clinically, the patients were examined for swelling and tenderness of joints (66/68) and for tenderness of 33 entheseal sites, and DAS28 and a MASES index (13 entheses) and were calculated, as measures of disease activity and entheseal involvement, respectively, at time of evaluation. Results: Twenty patients (18 women and 2 men, median age 54.5 (range 26-73) years and median disease duration 6 years (range 1-42)) were included. At baseline the median DAS28 was 4.69 (range 3.48-6.66) and the median entheses score (MASES) was 2 (range 0-8). Of the 400 entheseal sites examined by US, 108 (27%) showed abnormalities. A total of 148 US changes were seen of which 73 calcification/enthesophytes (49%), 60 erosions (40%) 12 thickened enthesis (8%) and 3 entheses with Doppler activity (2%). Overall, the entheseal sites of the lower limbs were the most frequently affected, 67%, versus 33% in the upper limbs. Clinically, only 14 patients had a positive MASES score but all the patients had B-mode changes, most frequently calcifications/enthesophytes and erosions and 3 patients had Doppler changes. The median number of entheses involved was 5 (range 1-9) and all patients had at least one entheseal site with abnormalities. The most frequently affected entheseal site was the trochanter region, whereas the inferior patella tendon was never involved. Conclusions: Entheseal abnormalities detected by US were frequent in RA patients. Although some of these changes may be on degenerative basis, 6 patients had at least 1 thickened enthesis and 3 had Doppler activity as a sign of inflammatory activity. This indicates that enthesitis may be a component of disease also in RA patients. Disclosure of Interest: None declared